Traumatology and functional recovery of the shoulder specific to the game of Volleyball - Ionite, Catalin; Stirbu, Ilie-Catalin; Stirbu, Catalin-Mihaela; Condurache, Iustina; Rotariu, Mariana (Balneo and PRM Research Journal (Online. English ed.), 2022)
Worldwide, the game of volleyball is a very popular sport regardless of the demographic categories analyzed. In recent years, the dynamics of the game of volleyball is continuously increasing, notable increases being observed among the female gender. Shoulder injuries are common among athletes, for example in baseball, 12% to 19% of injuries encountered are located in the shoulder, while in swimming, the percentage of shoulder injuries is estimated to be between 23% and 38%. The research is based on the case study carried out on a 28-year-old male subject, with 15 years of sports experience, a volleyball player, with a previous history of shoulder joint through the presence of bicipital tendinitis, contractures in the trapezius muscle, as well as in the the sternocleidomastoid muscle. The analysis of the dynamics of the evolution of the subject included in the research and the interpretation of the results led to the confirmation of the hypothesis, so that, reaching all the well-established recovery objectives, we can conclude that the symptomatology, in our case, rotator cuff muscle injury, can be combated by using kinetotherapeutic methods , which demonstrated the highest level of success achieved, when the subject can be taken even from the immobilization stage. Also, a much faster progress was observed from the point of view of socio-professional reintegration. Keywords: Volleyball, Shoulder, Recovery.